La universidad en la mira - Alvarado Dávila, Víctor (San José: Universidad de Costa Rica, Escuela de Estudios Generales, 2014)
En este ensayo se analizan críticamente, una serie de problemas que giran en torno a la metamorfosis de la educación superior del siglo XXI, en un ambiente global que permea la situación de las universidades en América Latina.La situación de transformación por la que transita la educación del siglo XXI, entendido como un fenómeno que  comparten los países latinoamericanos con otras esferas globales, genera una serie de problemas que, por más diversos que sean, adquieren sentido actualmente, si se estudian a la luz del interés mundial por globalizar la educación. En términos de creencia, con solo dar cuenta de algunos ejemplos aislados, por lo menos en lo que toca, puede ser suficiente para generalizar la situación por la que pasan, o han de pasar, las universidades de todo el mundo, máxime de que hoy en día la voluntad de poder de la globalización, se expande como una sombra sigilosa que, mientras más se mueve, adquiere cada vez más fuerza para arrastrar o someter a cualquier voluntad, en pro de su ideal de homogeneizar al planeta, en este caso, a través de la globalización de la educación universitaria. This   essay   examines,   critically,   a   series   of problems   related   with   the metamorphosis   of   higher   education   in   the   twenty-first   century,   in   a   global environment that permeates the situation of universities in Latin America. The situation of transformation that affects the XXI century education --understood as  a  phenomenon  that  is  shared  by  Latin  American  countries  with  other  global spheres --creates  a  series  of  diverse  problems,    that  make  sense  now,  if  you study  these  problems  taking  into  the  account  the  light  of  the  global  interest  in globalizing education. In terms of belief, with only check some isolated examples --at  least  in  what  concerns --is  enough  to  generalize  the  situation  by  passing,  or have passed, in the universities around the world;  especially now that day, when  the power of globalization moves or expands,  like a stealthy shadow that get more power    day  by  day  to  drag  or  submit  any  willingness  in  favor  of  his  ideal  of homogenizing   the   planet;   in   this   case,   through   the   globalization   of   higher education. This  article  pretend  analysis  the  regulation  on  the  Cubans  constitutionals texts  of 1901, 1940 and Constitutionals Statutes of Batista’s Government of 1952, as well as  in  its  complementary  laws,  of  the  inscription  in  electoral  register. Seeing  that, we analyses the different systems employed for the elector ́s inscription, whereas we  see  how  is  developing  the  register  institution,  owing  to  strengthen  of  the  all legal  and  institutional  environment  like  about the  same  is  to  take  shaping, gradually,  during  this  period.  Besides,  we  can  value  how  in  certain  moment  this institution  was  corrupted  in  its  political-social  task, turned  in  an  instrument  of  the political-administrative  corruption  prevailing  in  the  country,  for  the  commission  of electoral fraud. This  article  pretend  to  give  a  panoramic  about  the  content  of  the  confiability principle in registral subject. We approach the implications that this principle have for the information operated for the electoral registers, as well measures then make to  take  place  whit  the  objective  to  get  more confiability  high  levels.  In  this  sense, we  expose  experiences  that  base  fundamentally  in  the  use  of  biometry  and strengthen of  the  civil  register,  how  support,  this  last,  of  an  efficient  electoral register having in account the natural relationship between both. Besides, we offer a  detailed  analysis  of  the  breaking  off  points  Cuban  electoral  register  whit  the pointed principle. Finally,  we explain some general ideas that may contribute whit improve of the Cuban electoral register.